Future grid expansion planning towards cost-effective and sustainable ASEAN power grid development / Tofael Ahmed - Tofael, Ahmed (2018)
The efficient utilization of clean energy resources to meet increasing electricity demand is imposing the integration of the electricity market and the construction of secure transmission mechanisms around the globe. Accordingly, the Association of Southeast Asian Nations (ASEAN) is integrating its large geographical power transmission infrastructure via the ASEAN power grid (APG). Transmission expansion planning (TEP) is a complex and multidimensional because of a high number of uncertainties and influencing parameters. Therefore, it is very difficult to get a unique optimal transmission grid plan which maximizes the benefit and minimize the investment risks by satisfying all the technical, economic, social, and environmental constraints. During TEP process, assessing various scenarios like electricity generation capacity from renewable sources and fossil fuels, electricity demand, market prices, technological, social and environmental aspects are important to identify the uncertainties and minimize the risks. This study provides the building blocks of a TEP optimization methodology towards efficient APG development. Therefore, this study develops an optimal power flow, a minimum-cost power generation model, in MATLAB/MATPOWER simulation platform for simulating ASEAN energy market to evaluate the optimal development of APG infrastructure for 2030 generation and demand scenarios. Publicly available data are taken for the evolution of optimal cross-border power flows through the interconnections. An annual cost is used as the output matrix for to evaluate the feasibility of high voltage AC (HVAC) and high voltage DC (HVDC) transmission option for the cross-border interconnections links. Finally, a net market benefit framework to evaluate the benefit of APG establishment is developed by considering emission benefit of renewable generation. Developed net market benefit model also consider consumers, producers and transmission owner benefit. Results demonstrate that APG can enhance power generation from countries with abundant renewable resources to meet the growing demand at load centers in the ASEAN member nations. Moreover, transmission technology analysis results reveal that in some interconnections, implementing HVDC link instead of currently planned HVAC could be economically beneficial for the APG. Furthermore, benefit-cost evaluation reveals that APG transmission infrastructure with optimal cross-border transmission capacity is beneficial than APG with cross-border transmission capacity mentioned by ASEAN Center for Energy (ACE). Additionally, HVDC transmission options need overall less Yearly Required Revenue (YRR) than HVAC during APG establishment. Finally, the findings in this research would serve as valuable references for the power utilities and APG planners.